Study of a Neutral Hydrogen Feature Previously Observed by Cugnon - Mirabel Miquele, Igor Félix (1975)
An anomalous velocity cloud near l=349°, b=+3°, was investigated by Cugnon (1968). The authors made a new set of observations in order to obtain a more complete picture of the feature, including the region originally out of Cugnon's limit of observation. A comparison with optical and radio observations was made and several possibilities of interpretation as to the nature of the object were analyzed.